Studi Literature Pengetahuan Sikap dan Perilaku Orang Tua tentang Pemberian Makanan Bayi dan Anak (PMBA) Sesuai Tahapan pada 1000 Hari Pertama Kehidupan dalam Deteksi Resiko Stunting di Kalimantan Tengah - Desi Kumala; Etri Prilia; Sri Lilestina Nasution; Budi Subagiono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
One of the problems nutrition in Indonesia becomes the main concern when it is problem malnutrition in children under five gold is 1000 the first days of life (HPK). The stunting is still relatively high in Indonesia. And risk factors cause knowledge attitude and behavior in parents in giving food to fives and children (PMBA). This disruption influences mental and physical growth and the development of intelligence and cognition. This has children get nutrition intake as where should. 1000 HPK success is evident in nutritional status of sufficiency for children, in mark with growth and development by age physical and cognitive. Research objectives knowing a literature review of knowledge attitudes and behavior of parents of feeding infants and children (PMBA) 1000 according to the stage in the first days of life to decrease the risk of stunting in Central Kalimantan. The study results showed that the weight born and size of born the son are determined by the fulfillment of nutrients family when pregnant. Women born weighing low have a significant risk to be a mother who is stunted so that it will tend to give birth to a son with the weight of low birth as he does. Babies born with a stunted mom could be adult female who has stunted and will form the same cycle as before. Hence the importance of maintaining nutrition in the program, micro and macro, when pregnant mother and child after birth.